Reconsidering the Reliance on Functional Load: The Role of Phonetic Distance in Predicting L2 Segmental Substitutions - Kate Challis; Zoë Zawadzki; Ewa Kusz (Research in Language)
Much research agrees that Functional Load (FL), i.e., the extent to which a phoneme pair distinguishes between different words in a language, is a useful feature to consider in prioritizing phoneme pairs for pronunciation instruction in the second language (L2) classroom. However, FL measures are not always easy to access and are often calculated according to different principles, whereas other more easily observable features exist, including Phonetic Distance (PD), or the degree of physiological similarity between phones in a phoneme pair. One way to evaluate features and their interrelatedness is to use them in a linear mixed effects regression (LMER) model to predict the rate of observed L2 substitutions that are actually made in speech. This study examines the relationship between two measures of FL (Brown, 1988; Gilner & Morales, 2010) and an estimate of PD we devised from 22 unique articulatory features of vowels and consonants in their ability to predict substitutions in the L2-ARCTIC dataset (Zhao et al. 2018) while accounting for other sources of variation. It was found that even when PD had a resolution of only 2 points, it was highly associated with variance in substitution rates, but that the best model included FL and PD measures together. This finding suggests that PD may also be an important consideration when deciding which phoneme pairs to prioritize in L2 instruction.